Fully Copper‐Exchanged High‐Silica LTA Zeolites as Unrivaled Hydrothermally Stable NH3‐SCR Catalysts. Issue 12 (18th January 2017) - Ryu, Taekyung; Ahn, Nak Ho; Seo, Seungwan; Cho, Jung; Kim, Hyojun; Jo, Donghui; Park, Gi Tae; Kim, Pyung Soon; Kim, Chang Hwan; Bruce, Elliott L.; Wright, Paul A.; Nam, In‐Sik; et al.
Abstract: Diesel engine technology is still the most effective solution to meet tighter CO2 regulations in the mobility and transport sector. In implementation of fuel‐efficient diesel engines, the poor thermal durability of lean nitrogen oxides (NO x ) aftertreatment systems remains as one major technical hurdle. Divalent copper ions when fully exchanged into high‐silica LTA zeolites are demonstrated to exhibit excellent activity maintenance for NO x reduction with NH3 under vehicle simulated conditions even after hydrothermal aging at 900 °C, a critical temperature that the current commercial Cu‐SSZ‐13 catalyst cannot overcome owing to thermal deactivation. Detailed structural characterizations confirm the presence of Cu 2+ ions only at the center of single 6‐rings that act not only as a catalytically active center, but also as a dealumination suppressor. The overall results render the copper‐exchanged LTA zeolite attractive as a viable substitute for Cu‐SSZ‐13. Abstract : Age doesn't matter : Fully copper‐exchanged high‐silica LTA zeolites show unprecedented activity for selectively reducing NO x with ammonia, even after hydrothermal aging at 900 °C. Si yellow, O red, Cu blue.